CENTRAL OBESITY ASSOCIATED WITH CHARACTERISTICS OF VASOMOTOR SYMPTOMS IN MENOPAUS WOMEN - YUNIAR SETYAWATI; Ashon Sa’adi; Tiyas Kusumaningrum (SEAJOM: The Southeast Asia Journal of Midwifery, 2021)
Vasomotor complaints are common on postmenopausal women. Most women feel these complaints within 2 years after entering menopause; some of them will even feel up to a decade. In addition to vasomotor complaints, the incidence of central obesity also increases in menopause. The poor adipocyte system in central obesity that affects the central nervous system, body temperature and excessive sympathetic nerve activity have been suspected to be a cause of vasomotor syndrome at menopause. The purpose of this study was to analyze the relationship between central obesity and the characteristic of vasomotor symptoms in postmenopausal women. Method: this observational analytic study used a cross sectional design. The number of samples were 86 women aged 45-55 years who had been in postmenopausal period. Sampling technique was consecutive sampling. The independent variable was central obesity while the dependent variable was vasomotor symptoms. The data was taken using modified MENQOL questionnaire and direct measurements waist circumference to determine central obesity in the respondents. Data was tested using contingency coefficient test with α 0.05. Results: There were 59.3% respondents who experienced central obesity. More than eighty percent respondents with central obesity also experienced vasomotor symptoms which were considered disturbing. There was a significant relation between central obesity and the characteristic of vasomotor symptoms in postmenopausal women (p=0.00; r=0.513). Conclusion: The presence of central obesity leads to disturbing vasomotor symptoms in postmenopausal women